Transition phenomena of natural convection of the air in an asymmetrically heated vertical channel with a damper. (February 2022) - Kim, Koung Moon; Lim, Sun Taek; Kim, Seong Ho; Kim, Haeseong; Jerng, Dong-Wook; Ahn, Ho Seon
Highlights: Air natural convection in vertical parallel plates is investigated experimentally with controlling the damper installed at the end of the channel. Two different viewpoints of the transition phenomena in the natural convection are suggested based on the flow regimen change and flow pattern change. The change in the wall temperature distribution cannot be the basis to judge the flow regime change. In the entrance region, abnormal flow, such as recirculation flow and reverse flow, can appear below the middle height of the channel. In the fully developed region, the abnormal flow disappears, and the heat transfer performance can increase by the well-developed upward flow. Abstract: It was investigated the phenomenon of the air natural convection between vertical parallel plates with a damper installed at the end of the channel under asymmetrical heating conditions. The thermal behavior in the channel analyzed based on the vertically measured wall temperature distributions and bulk temperature distribution and the horizontal profiles of the air temperature measured at four heights. As the operating condition intensified, there was no change in either wall temperature distribution trend whereas the bulk temperature distribution trend changed only near the inlet through a change in the flow regime. This change in the flow regime affected the bulk temperature profile only near the wall. However, the overall temperature distributions and trends of the temperature profiles did not change drastically except near the inlet and they were similar to each other regardless of the operating condition and damper closing angle. On the basis of these results, it was focused on the transition phenomenon of natural convection between vertical parallel plates. It was considered the transition phenomenon from two viewpoints, that is, a change in flow regime and a change in flow pattern. In terms of a change in the flow regime, a distinguishable difference in the overall heat transfer performance was confirmed between laminar and turbulent regimes, but it does not affect the trends of the wall temperature distributions. Regarding the flow pattern change, criteria were suggested for distinguishing flow patterns between the entrance region and fully developed region at the mid-height of the channel according to the vertical temperature distributions and horizontal air temperature profiles. To verify the validity of the proposed concept, we made comparisons with the results of previous research and confirmed that our concept can be well applied.